High-Speed Counter-Current Chromatography in Separation and Identification of Saponins from Beta vulgaris L. Cultivar Red Sphere - Aneta Ewa Spórna-Kucab; Sławomir Wybraniec (Polish Journal of Food and Nutrition Sciences, 2020)
Saponins, natural plant compounds exhibiting health benefits, were extracted from B. vulgaris L. cultivar (cv.) Red Sphere and separated by high-speed counter-current chromatography (HSCCC) in a new solvent system composed of: TBME-BuOH-ACN-H2O (1:2:1:5, v/v/v/v ). The system was used in the head-to-tail mode. The flow rate of the mobile phase was 3 mL/min and the column rotation speed was 860 rpm. The retention of the stationary phase was 47%. The LC-MS/MS analyses were performed for the identification of separated saponins in the crude extract as well as HSCCC fractions,. Significantly different elution orders of the analytes were observed in the HSCCC and HPLC systems, indicating the complementarity of both the techniques in the fractionation of saponins. Moreover, during the HSCCC separation, acetal-type saponins were eluted faster than pentose/hexose-type saponins and then dioxolane-type saponins. The separation of saponins in the HSCCC solvent system enabled the fractionation and preconcentration of 13 saponins for further fragmentation experiments in the LC-MS/MS system. Nine saponins were detected for the first time ever in B. vulgaris L. cv. Red Sphere.